#TITLE_ALTERNATIVE# - HALIM (NIM : 234 10 013); Pembimbing : Ir. Hardianto Iridiastadi, MSIE, Ph.D , WINDA
Fatigue is a very important biological sign of body showing that the body needs to rest. Fatigue can be classified into two types are physical or physiological fatigue and mental fatigue or psychological. Mental fatigue associated with how people process information obtained as known as the Human Information Processing (HIP). This research will be done related to measurement of mental and motor skills related to known as psychomotor, using PVT (Psychomotor Vigilance Task). Measurement using PVT has been widely used abroad with a variety of purposes. However, studies using the PVT in Indonesia is still very rarely, so of course the research related PVT is needed to measure the fatigue of Indonesian people as well as the most sensitive parameter that can measure the fatigue. This study by two experimental, one experiment that uses the treatment of the midterm exam and experiment 2 with the treatment of a work sheet UKT (Uchida Kraepelin test). In both experiments were also carried out recording the VAS (Visual Analogue Scale) which is a subjective value of respondent fatigue. The data obtained in the experiment will then be processed using a statistical test to determine whether the PVT can detect fatigue, test results indicated that significantly different results. Statistical testing done in several ways, namely the first experiments performed by the Parametric Test using Paired Sample T-Test and Non-Parametric Test using the Wilcoxon Signed Rank Test, while in the second experiment performed statistical tests using the One Way Anova. Data testing parameters used were mean, standard deviation, maximum, minimum, range, variance, sum, and number of lapses. Data are processed into these parameters are the raw data, 10% slowest, and 10% fastest. Based on testing conducted, found that the PVT to the data before and after midterm exam results are not significant for all tests and parameters. For the second experimental parameters to yield significant results on all data using the parameters of the average and sum. Meanwhile, VAS always give significant results. These contradictory results may in fact not directly provide a conclusion whether the PVT can be used or not, due to the different conditions of data collection. Thus, conclusions can be drawn from this study is the PVT can be used to measure mental fatigue with laboratory research conditions and things become a critical factor in the study using the PVT is the initial condition of the respondent.